CARDIAC SURGERYThe role of balloon aortic valvuloplasty in the era of transcatheter aortic valve implantation - Wacławski, Jacek; Wilczek, Krzysztof; Pres, Damian; Krajewski, Adam; Poloński, Lech; Zembala, Marian; Gąsior, Mariusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Balloon aortic valvuloplasty is recommended in patients not suitable for transcatheter aortic valve implantation/aortic valve replacement (TAVI/AVR) or when such interventions are temporarily contraindicated. The number of performed balloon aortic valvuloplasty (BAV) procedures has been increasing in recent years. Valvuloplasty enables the selection of individuals with severe left ventricular dysfunction or with symptoms of uncertain origin resulting from concomitant disorders (including chronic obstructive pulmonary disease [COPD]) who can benefit from destination therapy (AVR/TAVI). Thanks to improved equipment, the number of adverse effects is now lower than it was in the first years after the advent of BAV. Valvuloplasty can be safely performed even in unstable patients, but long-term results remain poor. In view of the limited availability of TAVI in Poland, it is reasonable to qualify patients for BAV more often, as it is a relatively safe procedure improving the clinical condition of patients awaiting AVR/TAVI.